miR-151 Affects Low-Temperature Tolerance of Penaeus vannamei by Modulating Autophagy Under Low-Temperature Stress - Liang, QingJian; Dong, WenNa; Ou, MuFei; Li, ZhongHua; Liu, Can; Wang, FeiFei; Liu, Yuan; Wang, WeiNa (Frontiers in Cell and Developmental Biology, 2021)
MicroRNAs (miRNAs) play key roles in many physiologic and pathologic processes, including autophagy. Autophagy is cellular in an emergency response mechanism of environment stress, but their complex molecular regulatory mechanism under low temperature stress is largely unknown in shrimp, especially microRNA (miRNA)-mediated regulation of autophagy in low temperature tolerance. In this paper, a shrimp PvTOR and miRNA pva-miR-151 cooperation in response to low temperature stress have been reported. Pva-miR-151 showed expression patterns opposite to target PvTOR under low temperature stress. The miRNA pva-miR-151 targets the 3' UTR region of PvTOR, inhibiting the formation of autophagosome, which to degradative damaged the organelle. In addition, the low temperature tolerance was correlated positively with autophagy in shrimp. Silenced pva-miR-151 increased sensitivity to low temperature stress, whereas overexpression pva-miR-151 decreased the expression of PvTOR, p-TOR, and increased tolerance to low temperature stress by improving the formation of autophagosome and THC. In addition, the TOR activator 3BDO can partially rescue autophagy induced by overexpression of pva-miR-151, these results indicating that miR-151 was necessary for the low temperature tolerance in shrimp. Taken together, we provide a novel strategy and mechanism for shrimp breeding to improve shrimp low temperature tolerance.